The impact of workload and external locus of control on premature sign off audit mediated by emotional intelligence - Tatia, Tatia; Irdhayanti, Efa; Rosnani, Titik (Junal Ilmu Manajemen, 2025)
Auditors must be professionally responsible for clients completing their duties to produce audit reports because of the magnitude of client demands for the work performed by auditors. Inappropriate time pressures cause auditors to create work that is not optimal and cause auditors to take dysfunctional actions. This action can occur for many reasons, one of which is due to the high workload and the influence from within the auditor himself. Therefore, auditors must have high emotional intelligence to prevent this from happening. This study aims to ascertain and test the effect of workload and external locus of control on premature sign-off audits with emotional intelligence as a mediator. The population in this study are auditors with domiciles in West Kalimantan; the criteria are auditors who work actively in public accounting firms, companies, and government agencies. Data acquisition requires a sample of 74 auditors. Partial Least Square (PLS) is used to analyze data using the SmartPLS version 4 analysis tool.